Contribution to flood risk management by the IRIP method at the level of Gareat El Taref catchment, Constantine’s highlands, North-East of Algeria - Naouel Dali; Zouini Derradji; Breil Pascal (Journal of Water and Land Development, 2018)
The term flooding is often associated with a stream overflow or a marine flood, runoff-floods is rarely considered, and today suffers from a lack of knowledge and control of the phenomenon. This paper, presents a geographic information system iRIP@ – Flooding by Intense Pluvial Runoff (French acronym), which is a new tool to mapping flooding by runoff as a tool for decision-making by mapping runoff flooding in Gareat El Taref catchment (Northeast Algeria), with identifying the area of production, transfer and accumulation of flood.